Development of semi-autonomous mobile robot hardware-in-the-loop (HIL) simulation for indoor mapping - Saesar, Luhur Budi (2012)
Hardware-in-the-loop (HIL) simulation has widely been used among automotive industry, traffic control, robotics, unmanned vehicle and many other industries. HIL test became new trends in embedded system testing since they provide the advantageous factor such as cost, safety and duration, which is to be sought for most industries. In unmanned vehicle area, many robotics researchers have focused on the development of unmanned aerial vehicle (UAV) but not on unmanned ground vehicle (UGV). Hence, the research was intended to develop a control system architecture test for UGV using HIL simulation method. The research process had focused on control system architecture development based on HIL method along with kinematic-dynamic modeling, telemetry-visualization system and laser range finder (LRF) block in SIMULINK for mapping indoor environment. In this study, several tests were conducted to ensure the results meet the objectives. Telemetry test, sensing-mapping test and motion control test were done prior to the assembly system. The use of MATLAB SIMULINK toolboxes was to simplify the building, editing, monitoring and verifying the control system. The result was a control system architecture that applied HIL method and an alternative telemetry visualization. Kinematic-dynamic modeling was conducted to compare the path history between the simulation and the real test. An alternative telemetryvisualization system was achieved using the regular playstation joystick principle. From it an alternative sensor such as rotary encoder and inclinometer were able to be built. Furthermore, 3D virtual model of UGV and the environment test field were developed to ease the system monitoring. Finally, the control system architecture that was developed and proven would be useful for further development of UGV. Keywords : Hardware-in-the-loop; Simulation; SIMULINK; Unmanned Vehicle; Telemetry; Visualization.